"Nobody Came Down": The Effect of the Financial Crisis on Tourism in Two Roatán Communities. Issue 2 (1st June 2020) - Brown, Racine
Abstract: This article examines the effects of the 2008 financial crisis on the tourism sector in the communities of West End and Punta Gorda on the island of Roatán, Islas de La Bahia (Bay Islands), Honduras. This article is based on ethnographic field research conducted in these two communities from April 2011 to April 2012 for a dissertation project. This project is both biocultural and political ecological in nature and utilizes a mixed methods approach incorporating participant observation, semi‐structured interviews that delve into household livelihoods and foodways, and surveys that assess dietary diversity. Overall, the tourism sector on Roatán suffered a drastic setback from June of 2009 until 2010 and has recovered at different rates depending on the particular type of tourism work practiced by the household. Among other things, occupational group has a significant relationship with dietary diversity. From this research I make recommendations to improve income and dietary diversity for households engaged in sectors that have not recovered. This includes adjustments to cruise ship schedules to enable more souvenir and food sales, courses to improve local residents' marketability in higher paying tourism jobs such as scuba diving instruction, and community gardens to improve access to food and dietary diversity. The primary goal of this article is to spark discussion of the differential effects of the financial crisis on tourist receiving locations through the detailed presentation of one empirical example of these effects.